Genetic Color Morphs in the Eastern Mosquitofish Experience Different Social Environments in the Wild and Laboratory. (13th September 2016) - Kraft, Brittany; Williams, Emily; Lemakos, Valerie A.; Travis, Joseph; Hughes, Kimberly A.
Abstract: The social environment of an animal is an especially interesting component of its environment because it can be shaped by both genetic and non‐genetic variation among social partners. Indirect genetic effects (IGEs) are those created when genetic variation in social partners contributes to variation in an individual's phenotype; a potentially common form of IGE occurs when the expression of a behavioral phenotype depends on the particular genotypic combination of interacting individuals. Although IGEs can profoundly affect individual‐ and group‐level fitness, population dynamics, and even community structure, understanding their importance is complicated by two inherent challenges: (1) identifying individuals with genetic differences in social interactions that can contribute to IGEs and (2) characterizing natural social interactions that potentially involve IGEs. As a first step toward addressing both these challenges in the same system, we investigated social interactions involving genetically distinct male color morphs in the poeciliid fish Gambusia holbrooki under natural and laboratory conditions. Previous work indicates that melanic (M) and silver (S) males differ in social behavior and in how conspecifics respond to them, suggesting the potential for IGEs. We used a combination of live and video recording of social groups in two natural populations and in the laboratory to determine the potential for IGEs to contribute to behavioral variation in this species. We found that M males had more social partners, and especially more female social partners than did S males, in nature and in the laboratory. These results suggest that both direct and indirect genetic effects have the potential to play a role in the expression and evolution of social behavior in G. holbrooki .